Legal Protection of UMKM Associations under the Job Creation Law in North Bengkulu - Fransiska, Septi; Marlinah; Uswatun Hasanah (Universitas Islam Negeri Walisongo Semarang, 2024)
In the era of Society 5.0, Micro, Small, and Medium Enterprises (MSMEs) are a cornerstone in driving Indonesia's economic development, playing a critical role in increasing the Gross Domestic Product (GDP) and absorbing a significant portion of the workforce. In North Bengkulu, MSMEs face various challenges, yet these challenges also present opportunities for innovation and growth. The North Bengkulu MSME Association has initiated movements such as